A scalable in situ surfactant-free synthesis of a uniform MnO/graphene composite for highly reversible lithium storage. Issue 48 (24th November 2016) - Cai, Wenlong; Li, Gaoran; Zhang, Kailong; Zhou, Jianbin; Qian, Yitai; Du, Jin
Abstract : A scalable in situ surfactant-free synthesis of a uniform MnO/graphene composite was prepared, and exhibited large reversible capacity with long-term and superior rate performance. Abstract : A novel MnO/graphene composite, used as an anode for lithium ion intercalation, was prepared via an in situ surfactant-free facile method by taking advantage of the byproduct Mn ion in the conventional fabrication of graphene oxide. The as-fabricated lithium ion batteries exhibited a long-term stable reversible capacity (603 mA h g −1 after 350 cycles at 1 A g −1 based on the composite, hereinafter the same) and superior rate performance (400 mA h g −1 at 3 A g −1 ).